Motivasi Mantan Pekerja Yang Mengalami Pemutusan Hubungan Kerja Dalam Memulai Usaha Mikro: Studi Fenomenologi di Kota Semarang - Demina Fitrialisty; Fuad Mas’ud (Diponegoro Journal of Management, 2025)
This study aims to understand the motivations of former workers who experienced Termination of Employment (PHK) in starting microenterprises in Semarang. Microentrepreneurship plays an important role in the local economy, particularly by creating jobs and boosting economic growth. After experiencing PHK, many former workers chose to start microenterprises as an alternative to generate income. Factors motivating them include the drive for economic independence, utilisation of prior skills, and support from family and the government. However, the challenges they face include limited capital, difficulty in finding strategic business locations, and a lack of knowledge in marketing and financial management.A phenomenological research method is used to explore the subjective experiences of former workers, with data collection through in-depth interviews, observation, and documentation.The results indicate that while motivation and external support are important, the practical challenges faced by former workers remain significant. Therefore, government programs supporting microentrepreneurship, such as training and access to financing, need to be tailored to the specific needs of former workers to be more effective in helping them succeed in business.